2003
DOI: 10.1364/ol.28.000911
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-phase-matched second-harmonic generation in a GaAs/AlAs superlattice waveguide by ion-implantation-induced intermixing

Abstract: We report type I second-harmonic generation by use of first-order quasi-phase matching in a GaAs/AlAs symmetric superlattice structure with femtosecond fundamental pulses at 1.55 microm. Periodic spatial modulation of the bulklike second-order susceptibility chi(zxy)(2) was achieved with quantum-well intermixing for which the group III vacancies were created by As+-ion implantation. A narrow second-harmonic bandwidth of approximately 0.9 nm (FWHM) with an average power of approximately 1.5 microW was detected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…Shifts in the bandgap energy of 54 nm after IID were recorded. In nonlinear experiments, output second-harmonic powers exceeded 1 μW for the first time in DD-QPM waveguides and the conversion ratio was tripled over that of previous waveguides made by the silica cap method [78]. However, the conversion efficiency was still limited by the large optical losses (21 dB cm 1 ) at the fundamental wavelength which were caused by surface damage from etching the gold implantation mask off.…”
Section: Laser and Photonics Reviewsmentioning
confidence: 89%
“…Shifts in the bandgap energy of 54 nm after IID were recorded. In nonlinear experiments, output second-harmonic powers exceeded 1 μW for the first time in DD-QPM waveguides and the conversion ratio was tripled over that of previous waveguides made by the silica cap method [78]. However, the conversion efficiency was still limited by the large optical losses (21 dB cm 1 ) at the fundamental wavelength which were caused by surface damage from etching the gold implantation mask off.…”
Section: Laser and Photonics Reviewsmentioning
confidence: 89%
“…MicroRaman spectroscopy has confirmed that first-order gratings can be formed by this technique [82]. As a result, higher SHG conversion efficiencies were recorded [83,84]. We have continued the work on DD-QPM and have achieved even greater performance, which will be discussed in Sec.2.2.…”
Section: Periodically Intermixed Waveguidesmentioning
confidence: 89%
“…The vector q has a direction along the direction of the χ (2) modulation and the length of |q| = l c /Λ, where Λ is the spatial modulation period. The modulation of the nonlinearity can be accomplished by periodically inverting the sign of the χ (2) susceptibility, utilizing a zigzag optical path in slabs of nonlinear material with total-internal reflection [11,35,36] or by modulating the amplitude of the second-order susceptibility by periodically modifying the material properties, for instance, by employing quantum-well intermixing in GaAs-AlAs waveguides [37][38][39]. The latter two QPM methods have rarely been used so far either because of the relatively high losses as in the case of the totalinternal-reflection geometry, or due to the small thickness of the modulation which mandates a waveguide geometry for the frequency conversion device.…”
Section: Quasi-phase-matchingmentioning
confidence: 99%